Hydrolagus matallanasi sp. nov. (Holocephali, Chimaeridae) a new species of rabbitfish from southern Brazil - Soto, Jules M.r.; Vooren, Carolus M. (Zootaxa, 2004)
Hydrolagus matallanasi sp. nov., the first species of the genus in the southwest Atlantic, is described from 21 specimens collected on the continental slope of southern Brazilian at 416 736 m depth. This new species can be distinguished from its congeners by the following combination of characters: an irregular brown coloration with reticulations and spots over the body; ventral surface whitish, including pectoral bases; proximal margin of the second dorsal fin whitish; tooth plates striped and bicolor, yellowish and gray; length of dorsal fin spine equal to or a slightly longer than head length; pectoral fin notably long, its tip extending beyond posterior margin of pelvic fin base; upper margin of second dorsal fin notably concave at middle region of second dorsal fin base; second dorsal fin with minimum height less than half of its maximum height (located at points anterior and posterior to middle region of fin); eye length slightly smaller than preorbital length. The new species is compared to H. mirabilis, the most similar species from North Atlantic, and H. alberti, which occurs in the western Atlantic.